Entornos virtuales de aprendizaje y su impacto en el rendimiento académico en los estudiantes de educación básica de la Escuela Sebastián de Benalcazar, las Naves. 2021. - Merchàn Contreras, Liliana Lisbeth (2021)
Currently the study environment is an important factor that influences the academic performance of students, however, some parents give little importance to it, for this reason it is required that students can have an adequate learning space and this way they can improve their academic level. The present degree work called “Virtual Learning Environments and their Impact on Academic Performance in Basic Education Students of the Sebastián de Benalcazar School, las naves. 2021”, has the specific purpose of developing a proposal for the creation of a study environment that allows students to improve their academic performance. The problem that gave rise to the research is that the teachers of the Sebastián de Benalcazar school as a result of the pandemic have had to change their way of teaching, it is no longer in person but virtual, but this new study modality has generated inconveniences for teachers because many used another type of methodology to teach their classes as currently required by the government and for students because not all have a suitable environment to receive their classes due to certain factors that influence such as infrastructure , external and internal noises, the same ones that do not allow the total concentration of the students at the time of receiving their classes, thus affecting their academic performance. The general objective of the project is to establish virtual learning environments and their impact on academic performance in basic education students at the Sebastián de Benalcazar school, Las Naves